Implementation of the Master Plan Activities in Serayu River Voyage (SRV) Within the Framework of Tourism Development in Banyumas Regency - Pamungkas, Imam; Suryono, Agus; Sarwono, Sarwono (Journal of Indonesian Tourism and Development Studies, 2015)
The Master Plan Activity of Serayu River Voyage (SRV) for tourism development in Banyumas Regency were expected to be completed within five years from 2008 to 2012, but during the period until 2013, most programs and activities have not been implemented. The results showed that the Master Plan of SRV in the framework of tourism development in Banyumas Regency has not been implemented properly. The cause is the absence of good coordination between agencies, the lack programs and activities integration, supporting documents have not been revised, absence of good socialization, and the lack of private sector contribution. The factors that constrain and support implementation of the Master Plan is described as follows. Supporting factors: competent human resources (implementor) already available at the managerial level and have intellectual tourism, it is only need to add personnel in the sector of culture; the availability of adequate budget; institutions that have been effective and efficient; High community response; High commitment of Banyumas Regent and cooperation related parties (stakeholders); and natural conditions of Serayu tend to calm and the river slope condition is small. The constrain factors: regulatory policies; integration of programs and activities; coordination and socialization implied sectoral ego that need to be addressed. Keywords : implementation, master plan, Serayu River Voyage, human resources, regulation